Design Data Warehouse for Centralized Medical Record - Permana, Kadek Ary Budi; Subiksa, Gde Brahupadhya; Sudarma, Made (International Journal of Engineering and Emerging Technology, 2018)
Medical record is a note related to service and action which was accepted by the patient on the health facility. Nowadays, data about medical record have been saved electronically both in form of computer file or database file. Today, the medical record can only be accessed by the hospital and the patients themselves. Medical record supposed to be a consideration in taking particular medical action in real situation. The centralized medical record is needed in order to ease the exchange of medical record among hospitals or other institute.  The centralized medical record will involve a lot of data from many sources. The design of the data warehouse can be a solution, in which the data warehouse is a place to submit the data or the data which have been submitted systemically so it can be used to help the analysis and report. By designing the centralized medical recorded it is expected that in the future it can give the complex information and analyzing the data.